Quality of Public Services at the Public Company of the Regional Drinking Water (Perumdam) Tirta Berkah Labuan Branch - Supriatno, Eko; Damara, Muhamad Allam (Lenggogeni Data Publishing, 2025)
This study aims to analyze the quality of public services at the Tirta Berkah Regional Public Company of Drinking Water (PERUMDAM) Labuan Branch, as well as identify obstacles and efforts made by the company in improving the quality of service to the community. The research method used is a qualitative approach with data collection techniques through observation, interviews, and documentation. Data analysis is carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of the study show that the quality of public services at PERUMDAM Tirta Berkah Labuan Branch has not been fully optimal. Of the five public service indicators used as a reference—tangible evidence, reliability, responsiveness, assurance, and empathy—the empathy indicators still show weaknesses, especially in the responsiveness of officers to customer problems. The main problem faced by customers is water distribution disruptions such as dead water and turbid water that has not been completely resolved. In addition, there have been no significant steps from the company to suppress these complaints. Thus, improving the competence of officers and evaluating the water distribution system is an urgent need to improve the quality of public services in a sustainable manner.